Nonlinear Forced Vibration of Bidirectional Functionally Graded Porous Cylindrical Shells in Thermal Environment using First-Order Shear Deformation Theory - Rahmani, Ahmad Ali; Hosseinnejad, Farhad; Rostamiyan, Yasser (Journal of Applied Nonlinear Dynamics, 2026)
The primary focus of this article is to examine the nonlinear forced vibrations of cylindrical shells made of bidirectional functionally graded porous (BDFGP) material. These shells are surrounded by elastic foundations and subjected to a thermal environment. BDFGP shell properties are assumed to be temperature-dependent and change continuously in terms of thickness and length. The governing equations are derived based on the first-order shear deformation theory (FSDT) and the von Kármán strain-displacement relations to analyze the system's dynamic behavior. These equations describe the transverse motion of the shell. The Galerkin discretization method is then applied to obtain the final governing equation for the structure's transverse motion. The multiple time scales method is utilized to solve the governing equation and determine the nonlinear frequency response of the shell. This method provides an equation that allows for the calculation of the nonlinear frequency response. In order to validate the accuracy of the obtained results, the system frequencies are computed under various conditions and compared with the findings of previous studies. Once the accuracy is confirmed, a parametric study is conducted to assess the impact of different parameters on the nonlinear frequency response of the BDFGP cylindrical shell.